Continuous professional development and student support in an open and distance e-learning institution: a case study - Modise, Mphoentle Puleng (International Journal of African Higher Education, 2020)
Faced with emerging technologies and a diversity of students entering higher education in South Africa, lecturers must continuously equip themselves with the necessary skills to teach and support today’s learners effectively. This article reports on the lessons learnt and experiences of academics at an open distance learning (ODL) institution who participated for the first time in the fully online teaching and learning programme at an international institution, through a partnership aimed at developing academic capacity in ODL. The author suggests that academics cannot impart and transfer to learners skills they themselves do not possess, and makes recommendations for striving towards an effective student support system through continuous professional development in distance education and e-learning. The study revealed that the participants appreciated the support they received and valued the skills acquired in the programme. They also indicated that they were planning to use the new skills to enhance their own teaching. The study followed a case study methodology and made use of a range of data collection methods and tools that are in line with qualitative studies. Keywords: continuous professional development (CPD), distance education, e-learning, student support, open and distance e-learning (ODeL), transactional distance, community of inquiry (CoI)